From Apprenticeship to Internship: The Social and Legal Antecedents of the Intern Economy - Alexandre Frenette (tripleC: Communication, Capitalism & Critique)
This article looks towards the future of the intern economy by focusing on its past. What led to recent debates about the intern economy? How did it become legally possible for interns to work for free? Using the United States as my case study, I draw parallels between the current intern economy and its closest historical antecedent, the apprenticeship system. By providing a brief overview of the history of work-based learning and the unpaid internship’s legal underpinnings, this article ultimately frames current lawsuits and debates as a correction to today’s insufficiently scrutinized youth labour regime not unlike the apprenticeship systems of the past. In the attempt to facilitate youth transitions from school to work, yet maintain minimum wage standards, government intervention and—more imminently likely—legal decisions will, I anticipate, eventually transform the intern economy much like the Fitzgerald Act of 1937 drastically formalized apprenticeships in the United States.